Suppose -5*z = -3*z + 2*o + 126, 4*z + 3*o + 250 = 0. Let n = 27 + z. Let u = -19 - n. Solve i - u = 4*i for i.
-5
Let u be (-16)/(-6) + (-4)/6. Suppose -41*f + 19 = -63. Solve -p + u = -f*p for p.
-2
Suppose 2*u = 6*u - 40. Let p be (0 + (0 - 1))*5. Let v = -1 - p. Solve -v*m = -9*m + u for m.
2
Suppose 3*j = -u + 5*j - 5, 5 = 3*u - j. Solve -12 = i + u*i for i.
-3
Suppose -4*i + 4 = 0, -4*g + 5*i = 4*i - 35. Suppose 4*b + 4 = 2*o, -2*o + 0*o + 4 = 3*b. Solve -3*a = -b*a - g for a.
3
Let j = 14 - -12. Let r be 6⁄39 + 126/j. Solve r*m - 11 = -1 for m.
2
Let j be (-3)/(-6)-2 + -3. Let f be 3/j(4 + -12). Solve -l + f = 2 for l.
4
Let l be 16/(-24) + (-22)/(-6). Solve 1 - 4 = -l*o for o.
1
Let x = -21 + 27. Solve -x + 3 = j for j.
-3
Let v = -2 + 4. Solve 3*p - v = 1 for p.
1